The Use of Gemini AI in Teaching Speaking "Gemini AI as a Speaking Coach: Transforming EFL Speaking Practice" - Rachman, Lukman Arif (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
This study investigates the effectiveness of Gemini AI in teaching speaking skills to second-grade senior high school students in Bandung. The study aims to reveal the use of Gemini AI in teaching speaking abilities. The participants consisted of 24 students and one English teacher from one of the private high schools in Bandung; most of the students possessed an intermediate level of speaking proficiency. The study used Classroom action research for three three-cycle implementations. Each cycle consisted of planning, implementation, and evaluation, aiming to get betterment in implementing Gemini AI in teaching speaking. The instruments used in the study were an observation sheet and a researcher's journal in order to know the steps and the techniques used in implementing Gemini AI for teaching speaking in every cycle. Findings from this research demonstrate that Gemini AI can be used as a tool in speaking lessons, providing interactive, real-time feedback and practice opportunities. Even though the implementation faced some obstacles, there were always some improvements in every cycle, which led the teacher and students to make Gemini AI as an effective digital tool for enhancing students’ speaking skills. The significance of the study indicates that integrating AI in teaching speaking can provide individualized and interesting language practice. The use of artificial intelligence in teaching speaking also can enhance conventional teaching strategies. This study contributes to the growing body of literature on AI in education and provides practical implications for English language teaching, especially in enhancing students’ communicative competence.